2014
DOI: 10.3126/kumj.v10i4.11009
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Cocoon in an Adolescent Male

Abstract: Abdominal cocoon is an uncommon peritoneal condition characterized by partial or complete encasement of small bowel by a thick rind of fibrous tissue and adhesions. Only few cases of this disease have been reported in world literature. The etiology of this condition is unknown, and most often it is found in adolescent girls from tropical or subtropical countries, and usually diagnosed incidentally on exploration. Surgery (membrane dissection and extensive adhesiolysis) is the treatment of choice. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…[ 38 ] Small intestines barium transit reveals collected and conglomerated bowel loops in the center of the abdomen, suggestive of the so called “cauliflower sign.” [ 32 ] Additionally, prolonged transit time encourages the diagnosis. [ 33 ] Abdominal ultrasonography may reveal dilated bowel segments surrounded in a dense fibrous membrane, as well as free abdominal fluid and a thicker peritoneal layer. [ 38 , 39 ] On CT, which is the most useful tool in confirming the diagnosis, the appearance of small intestine segments that are conglomerated at the midline and surrounded by a thick capsule with a contrast-free periphery is a distinctive sign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 38 ] Small intestines barium transit reveals collected and conglomerated bowel loops in the center of the abdomen, suggestive of the so called “cauliflower sign.” [ 32 ] Additionally, prolonged transit time encourages the diagnosis. [ 33 ] Abdominal ultrasonography may reveal dilated bowel segments surrounded in a dense fibrous membrane, as well as free abdominal fluid and a thicker peritoneal layer. [ 38 , 39 ] On CT, which is the most useful tool in confirming the diagnosis, the appearance of small intestine segments that are conglomerated at the midline and surrounded by a thick capsule with a contrast-free periphery is a distinctive sign.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 97 articles were included in our study. [3–41] The flow diagram of the study is shown in Figure 4. These articles were carefully studied, and a database with the patients’ characteristics was made, which could be available if requested.…”
Section: Methodsmentioning
confidence: 99%
“…Although the triggering factors are yet to be determined apart from few theories that have been there since this syndrome has been first described but yet to be proven or supported hence the name primary. The most wildly mentioned theories being retrograde menstruation with a superimposed viral infection, retrograde peritonitis via the fallopian tubes, and cell-mediated immunological tissue damage secondary to gynecological infection [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] .…”
Section: Discussionmentioning
confidence: 99%
“…However, case reports from temperate zones have been reported in all age groups regardless of gender. 15,16 The aetiology of the abdominal cocoon is poorly understood. Various theories have been proffered, including retrograde menstruation with a superimposed viral infection, retrograde peritonitis, and cell-mediated immunological tissue damage incited by gynaecological infection.…”
Section: Discussionmentioning
confidence: 99%